Unloading damage evolution and rockburst risk assessment of Xuefengshan No.1 tunnel by combining multiple approaches - Guo Xiang; Xiaohua Zhang; Shengnian Wang; Zhijian Wu; Xinming Pan; Dehui Xu (Scientific Reports)
Abstract Large-scale rock burst disasters often occur in high-stress and deep-buried tunnels, due to challenges in accurate forecasting and the lack of clarity regarding the underlying mechanisms largely. This study combined on-site stress drilling tests, coupled finite and discrete element simulations, and theoretical calculations to examine unloading damage, rockburst evolution, and deformation failure of the high-stress and deep-buried Xuefengshan No.1 tunnel. The initial geo-stress characteristics were inversed to explore the unloading damage evolution and failure mechanism. The influences of stress distribution, displacement development, and energy release on the stability and rock burst risk of surrounding rock masses were analyzed. The rock burst risks along this tunnel were assessed by the energy method and stress intensity ratio method comprehensively. The findings revealed that displacement convergence and stress release caused by unloading during tunnel excavation were most prominent at the tunnel invert and the arch waist on both sides. The displacement of the rock mass within the unloading zone exhibited a symmetrical distribution along the tunnel axis, with displacement gradually decreasing radially outward. The deep-buried granite and slate sustained greater damage during the rockburst compared to sandstone. There were approximately 6500 m of the Xuefengshan No.1 tunnel, accounting for 55.7% of its total length, possessing potential rock bursts, predominantly at weak to moderate levels. The likelihood of rock bursts increased with burial depth, with a marked rise in risk when the depth exceeded 300 m. The results of this study could provide valuable insights into the geo-stress characteristics and rockburst risk assessment for high-stress and deep-buried tunnels.